Keterlibatan Pembelajaran Online Mahasiswa FKIP Selama Pandemi Covid-19 Berdasarkan Gender dan Domisili : Analisis Dengan Metode Rasch - Debora Debora; Wiyogo Wiyogo (Jurnal Ilmiah Kanderang Tingang, 2023)
This study aims to analyze the online learning activities that are most often carried out, the constraints that students have, responses to online learning and students' understanding of the material delivered by lecturers. This study used a survey method using an online questionnaire with the Google Forms platform. This research was conducted at FKIP Palangka Raya University with a total of 34 students. The sampling technique used is simple random sampling with a sample of all students. Data collection techniques through questionnaires, observation and documentation. Test the validity of the items in this study using the content validity test while the reliability test using the test-retest technique. The application of online learning at the FKIP of Palangka Raya University uses the zoom application in the form of learning by lecturers providing explanations of material. The obstacle that students have in online learning is a weak internet network, because the majority of students live in areas with poor signal. As a result, students have a lack of understanding of the material presented by the lecturer. This online learning is very good to use, it's just that it has to be supported by adequate infrastructure and training needs to be provided for lecturers who are unable to explore the use of technology.